A mathematical model for risk assessment based on the structure of the air transport of the complex to account for the specifics of air transportation and information system - Міщенко, А. В. (Science-based technologies, 2014)
A mathematical model for risk assessment based on the structure of the air transport complex to account for the specifics of air transportation and information system. Considered aspect of perfection (modernization) of existing system Air Transport lifecycle, which is crucial to ensure effective implementation of innovations in terms of restrictions on the budget development.